2010
DOI: 10.1002/app.32886
|View full text |Cite
|
Sign up to set email alerts
|

Narrow size‐distribution poly(methyl methacrylate) nanoparticles made by semicontinuous heterophase polymerization

Abstract: The effect of surfactant (sodium dodecyl sulfate) concentration on particle size, molar masses, glass transition, and tacticity of poly(methyl methacrylate) (PMMA) nanoparticles synthesized by semicontinuous heterophase polymerization under monomer-starved condition at constant monomer feeding rate is reported. Starved conditions are confirmed by the low amount of residual monomer throughout the reaction and by the fact that the instantaneous polymerization rate is similar to the feeding rate of monomer. Under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(57 citation statements)
references
References 36 publications
9
46
2
Order By: Relevance
“…Then, ultrasound has an important effect on kinetics polymerization by facilitating monomer diffusion between phases and decreasing particles sizes, as will be [22] studied the effect of surfactant concentration in the heterophase polymerization of MMA using only SDS as surfactant, and found that instantaneous conversion increases with SDS concentration, which supports the assumption of chain transfer to HBC10 in our experiments.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Then, ultrasound has an important effect on kinetics polymerization by facilitating monomer diffusion between phases and decreasing particles sizes, as will be [22] studied the effect of surfactant concentration in the heterophase polymerization of MMA using only SDS as surfactant, and found that instantaneous conversion increases with SDS concentration, which supports the assumption of chain transfer to HBC10 in our experiments.…”
Section: Resultssupporting
confidence: 80%
“…On the other hand, Aguilar et al [22] found a D pz value of 29 nm (R a = 0.15 g/min and polymer content of 22 %) using only SDS as the surfactant in a concentration of 3 %; P/S was 10. The corresponding D pz value obtained in the present work for Run 6 was 39 nm (R a = 0.2 g/min and polymer content of 21 %) with P/S = 13 and surfactant concentrations of 1.6 %.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This is contrary to what is normally expected for a conventional surfactant. For example, Aguilar et al [20] used SDS as surfactant to polymerize MMA by semicontinuous heterophase polymerization under monomer-starved condition at constant monomer addition rate. They found molar masses much lower than those expected from termination by chain transfer to monomer, which is the typical termination mechanism in 0-1 emulsion and micro-emulsion polymerization of this monomer.…”
Section: Resultsmentioning
confidence: 99%
“…When the weight ratio of AIBN to MMA is kept constant, the molecular weight of PMMA nanolatex particles increases substantially with the increasing MMA concentration (Group D). At a MMA concentration of 315 mg mL À1 , the molecular weight of PMMA nanolatex particles increases to 39.6 Â 10 5 g mol À1 , which is much larger than those of PMMA nanolatex particles fabricated via the KPS-initiated semi-continuous heterophase polymerization [10,27]. Finally, most PMMA nanoparticles display a fairly narrow molecular weight polydisperisity.…”
Section: Gpc Analysismentioning
confidence: 94%